BOOK REVIEW: TECHNOLOGY IN SECOND LANGUAGE WRITING: ADVANCES IN COMPOSING, TRANSLATION, WRITING PEDAGOGY AND DATA-DRIVEN LEARNING - Samsudin, Samsudin; Wattihelluw, Nurlaila; Supriadin, Supriadin; Answo Djedelbert Lao, Yandres; Sukarismanti, Sukarismanti (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This book provides a comprehensive exploration of the integration of technology in second language (L2) writing instruction. It examines the evolution of technology’s role in L2 learning, particularly in writing, where individual practice is crucial. The book consists of 11 chapters encompassing research and development reports on the application of technology, especially machine translation (MT), in the L2 writing learning process. While 90% of the content focuses on research results, a conceptual review in one chapter highlights the limitations of MT in English as a foreign language (EFL) writing. The book caters to L2 teachers and language learning researchers, offering valuable insights into using MT and wiki writing as effective learning instruments. Additionally, it presents novel strategies, such as using Wikipedia to hone critical thinking skills, and introduces handwriting automation for L2 writing assessment. Despite its merits, the book’s structure, content balance, and limited readership accessibility are areas requiring improvement. Nonetheless, its research findings and practical implications make it a valuable resource for L2 educators seeking to harness technology in writing instruction.